An assessment of India’s energy transition: Paris and beyond - Jairaj, Bharath; Kumar, Parul (Jindal global law review, 2019)
Since the signing of the Paris Agreement in 2015, climate change has gained greater prominence as a topic of importance in both public international law as well as national law. The energy sector has been at the forefront of deliberations on climate change, and the commitments made by parties to the Paris Agreement. India is going through an energy transition, straddling its broad commitments under the Paris Agreement with the specific challenges of providing universal, clean, and reliable energy to its citizens. Indian policymakers have been tasked with the challenge of making, monitoring, and enforcing effective laws to fulfil the overarching pledges made at the international level, while distilling them into national and sub-national law and policy, on a subject-matter that is the domain of legislation by both the centre and the states. This article explores some themes arising from this transition, examining the extant legal and regulatory framework governing issues at the intersection of the environment and energy. The authors undertake an evaluation of the successes and failures of schemes such as ‘Saubhagya’ and ‘Ujjwala’ aimed at energy access, and the rooftop solar PV scheme aimed at decentralized energy, and offer some recommendations to policymakers. Some of the recommendations include the framing of an approach based on a better appreciation of externalities and co-benefits, strengthening regulations and regulatory approaches, and the employment of a rich inter-disciplinary approach for making laws. The article aims to provide an overview of some of the more crucial issues in India’s energy sector and inform future research on regulation and policy-making in the field.